67Gallium scanning in the diagnosis of liver disease. Issue 5 (May 1974) - James, Oliver; Wood, E. J.; Sherlock, Sheila
Abstract : 67 Gallium ( 67 Ga) citrate liver scanning has been carried out on 60 selected patients following a scan with a radioactive colloid preparation. The 67 Ga scan correctly identified the site of primary liver carcinoma in 14 of 16 patients, including nine of 10 patients in whom the carcinoma arose in a cirrhotic liver, whereas a colloid scan positively identified the site in only four of these 10 cirrhotic subjects. Alpha-1-fetoprotein estimation was positive in eight of the 16 patients, including the two in whom 67 Ga scanning was negative. No positive 67 Ga scans were seen in 15 patients with cirrhosis but no primary liver cell cancer in whom a space-occupying lesion could not be excluded on colloid scan. 67 Ga citrate scanning appears to be the most reliable investigation available in the diagnosis of primary liver cell cancer. Uptake of 67 Ga in secondary metastatic tumours within the liver was less frequent, and appears to have much less value in the detection of these lesions and of bile duct carcinoma than in primary liver cell carcinoma. The 67 Ga scan was positive in six out of six patients with pyogenic abscess either in the liver or adjacent to it. In four of these patients a preceding colloid scan had shown no definite filling defect in the liver.